EXPLORING EFL TEACHER’S AND STUDENT’S CHALLENGES IN REMOTE LEARNING CONTEXT IN TABANAN, BALI - Hery Santosa; I Gede Putu Dharma Dewangga Putra; Ni Putu Astiti Pratiwi (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTThis descriptive qualitative study aimed to investigate the challenges faced by and strategies used by EFL teachers and students to cope with the challenges in implementing online remote learning. A public school in Tabanan was chosen as the setting of the study, with a teacher and five students as the subjects based on two criteria, namely activeness, and participation. The data were collected through observations and interviews to determine the challenges and the strategies used by the teacher and the students. The data were analyzed by using Interactive Model Analysis. The results indicated that the challenges the teacher and the students faced were mainly related to the platforms being used and the network connection. However, the teacher also faced a prominent challenge related to the student's motivation in learning. Several strategies were used by the teacher and the students, mainly solving the issue related to the network connection. The study results indicated the need for proper infrastructure and the teacher’s ability to support remote learning. ABSTRAKStudi kualitatif deskriptif ini bertujuan untuk menyelidiki tantangan yang dihadapi oleh guru dan strategi yang digunakan baik oleh guru maupun siswa pembelajar Bahasa Inggris sebagai Bahasa asing dalam mengatasi tantangan dalam pelaksanaan pembelajaran jarak jauh. Sebuah sekolah negeri di Tabanan dipilih sebagai latar studi ini, dengan seorang guru dan lima siswa sebagai peserta dalam penelitian ini dengan mempertimbangkan kriteria yaitu: keaktifan dan partisipasi. Data dikumpulkan melalui observasi dan wawancara untuk mengetahui tantangan dan strategi yang digunakan oleh guru dan siswa. Data dianalisis dengan menggunakan analysis model interaksi (Interactive Model Analysis). Hasil penelitian menunjukkan bahwa tantangan yang dihadapi oleh guru dan siswa sebagian besar terkait dengan platform yang digunakan dan koneksi jaringan. Namun, guru juga menghadapi tantangan yang menonjol terkait motivasi siswa dalam belajar. Ada beberapa strategi yang digunakan oleh guru dan siswa terutama untuk menyelesaikan masalah yang berkaitan dengan koneksi jaringan. Hasil penelitian menunjukkan perlunya infrastruktur yang layak dan kemampuan guru untuk mendukung pembelajaran jarak jauh.